THE CONCEPT OF COALITION AND OPPOSITION IN INDONESIAN DEMOCRACY - Baikal Firdaus; Hotmatua Paralihan (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the dynamics of coalition and opposition within Indonesia’s multiparty presidential democracy, with particular attention to the implications of coalition dominance for democratic accountability, legislative oversight, and policy quality. The research is motivated by the tendency of political parties in Indonesia to form broad governing coalitions, often driven not only by programmatic alignment but also by short-term political interests, access to executive positions, and strategic bargaining. Using a literature review with an interpretive-phenomenological approach, this study analyzes scholarly works, electoral developments, and coalition configurations from the post-2004 direct presidential election era to the 2024 political transition. The findings indicate that coalitions are essential for maintaining governmental stability in a fragmented multiparty system; however, oversized coalitions may weaken the institutional role of opposition parties and reduce the effectiveness of checks and balances. A weak opposition can also increase the risk of power concentration, limit alternative policy debates, and diminish public control over government decisions. At the same time, political fragmentation may create legislative deadlock when coalition management is not supported by programmatic consistency and institutional discipline. This study argues that a healthy democracy requires a proportional balance between governing coalitions and constructive opposition. Strengthening opposition functions, improving coalition ethics, and encouraging issue-based political cooperation are necessary to enhance democratic consolidation, prevent abuse of power, and ensure that coalition politics remains oriented toward public welfare rather than merely elite interests.